Population Pharmacokinetic Studies of Digoxin in Adult Patients: A Systematic Review - Abdel Jalil, Mariam; Abdullah, Noura; Alsous, Mervat; Abu-Hammour, Khawla (European journal of drug metabolism and pharmacokinetics, 2021)
Background Digoxin is a cardiac glycoside that was introduced to cardiovascular medicine more than 200 years ago. Its use is associated with large variability, which complicates achieving the desired therapeutic outcomes. Objectives To present a synthesis of the available literature on the population pharmacokinetics of digoxin in adults and to identify the sources of variability in its pharmacokinetics. Methods This is a PROSPERO registered systematic review (CRD42018105300). A literature search was conducted using the ISI Web of Science, Science Direct, PubMed, and SCOPUS databases to identify digoxin population pharmacokinetic studies of adults that utilized the nonlinear mixed-effect modeling approach. Results Sixteen articles were included in the present analysis. Only two studies were conducted in elderly subjects as a separate population. Both the pharmacokinetics and pharmacodynamics of digoxin were investigated in one study. Furthermore, the reviewed studies were mostly conducted in East Asian populations (68.8%). Digoxin's pharmacokinetics were usually described by a one-compartment model because of the nature of the collected data. Weight, age, kidney function, presence of heart failure, and co-administered medications such as calcium channel blockers were the most commonly identified predictors of digoxin clearance. The value of apparent clearance in a typical study individual ranged from 0.005 to 0.2 l/h/kg, while the value of the apparent volume of distribution ranged from 3.14 to 15.2 l/kg. The quality of model evaluation was deemed excellent only in 31.3% of the studies. Conclusion This review provides information about variables that need to be considered when prescribing digoxin. The results highlight the need for prospective studies that allow two-compartment pharmacokinetic/pharmacodynamic models to be established, with a special focus on the elderly subpopulation.